Alfonso X of Castile-León : royal patronage, self-promotion and manuscripts in thirteenth-century Spain - Kennedy, Kristin (Amsterdam University Press, 2019)
Today, the literary patronage of Alfonso X 'the Learned' of Castile (1252-1284) seems extraordinary for its time in the context of Europe. His cultural programme, which promoted his royal status and imperial ambitions, was hugely ambitious, and the paucity of information about the intellectual circumstances in which it took place magnifies the scope of Alfonso's achievements still further. This book argues that rather than providing a new cultural template for his kingdoms, Alfonso did little to promote institutional learning and preferred instead to direct the literary works he commissioned to a restricted, courtly audience who would understand the complex layers of symbolism in the representations of him that accompanied the texts. Despite this careful control, this book cites codicological and paleographical evidence to show that some codices traditionally ascribed to the royal scriptorium were copied at the behest of readers beyond the king's immediate circle.
Figure 1: Alfonso, wearing the livery of the royal Order of Santa María de la Estrella, with scribes, singers, and musicians. Cantigas, códice rico, Escorial MS T.I.1, fol. 5r. © Patrimonio NacionalFigure 2: Type and anti-type: the early years of Nebuchadnezzar (below), whose life prefigures that of Alfonso (above). General estoria IV, BAV Urb. Lat. 539, fol. 2v. Reproduced by permission of the Biblioteca Apostolica Vaticana, with all rights reserve
Keywords: Alfonso -- X, -- King of Castile and Leon, -- 1221-1284.; Alfonso -- X, -- King of Castile and Leon, -- 1221-1284 -- Books and reading.; Alfonso -- X, -- King of Castile and Leon, -- 1221-1284; Authors and patrons -- Spain -- History.; Books and reading -- Spain -- History.; Spain -- Intellectual life -- 711-1516.; Écrivains et mécènes -- Espagne -- Histoire.; Livres et lecture -- Espagne -- Histoire.; Espagne -- Vie intellectuelle -- 711-1516.; Early history: c. 500 to c. 1450/1500.; HISTORY -- Europe -- Spain & Portugal.; Authors and patrons; Books and reading; Intellectual life; Spain; 711-1516; Alfonso X.; Spain.; iconography.; manuscripts.; medieval.; History